Steel Structures Research Update: Steel-Concrete Composite Beams at Ambient and Elevated Temperatures - Liu, Judy (Engineering Journal, 2016)
Ongoing and recently completed research on steel-concrete composite beams and floor systems at ambient and elevated temperatures is presented. The research highlighted here includes investigations into shear connector slip, composite beams with high-strength steel, and tests of real-scale composite floor systems subjected to fire and structural loading.